EFFICACY OF METHODOLOGICAL PRACTICES UNDERTAKEN BY SAUDI ENGLISH TEACHERS IN PUBLIC SCHOOLS DURING THEIR FORMATIVE PHASE - Majed Othman Aba Hussain; Muhammad Iqbal; Imran Khan (University of Kuningan, 2019)
The main focus of this article is to evaluate the practices involving various approaches and methods that the novice Saudi English Teachers (SETs) employ in classrooms, and to see how far these are successful in attaining the desired results. It also takes into cognizance the chasm between the measures taken by Saudi Ministry of Education to modify the curriculum to develop communicative competence and the actualization these measures in the classroom pedagogy. The dichotomy eventually brings to bear upon the learning outcomes of the students who fail to achieve the required proficiency in communicative skills. The study necessitated a qualitative approach (grounded theory) in which previous literature was ransacked. Data was gathered through structured interviews, surveys and documents analysis. The rudimentary results showed that SETs rely more on conventional teaching methods despite the States thrust on Communicative Language Teaching (CLT) that tends to be more student-centered, cooperative and collaborative.